Quantification Of Oleoresin In Agarwood By Means Of Micro-Computed Tomography And Digital Image Processing - Khalid, Khair'iah Yazid @ (2011)
Micro-focus X-ray computed tomography is a powerful non-destructive scanning technique to study internal micro-structure in wood. In this thesis, the study contains two parts. The first part involves the reconstruction of an image from CT projections. An algorithm referred to as XRecon program has been developed to allow slice reconstruction for parallel beam and fan beam data. The program was created based on filtered back-projection method. An experimental CT setup (NMXCT) was built by utilizing medical digital radiography scanning system in Malaysian Nuclear Agency.